1998
DOI: 10.2337/diabetes.47.11.1771
|View full text |Cite
|
Sign up to set email alerts
|

Role for heparin-binding growth factors in glucose-induced vascular dysfunction.

Abstract: Vascular hyperpermeability and excessive neovascularization are hallmarks of early and late vascular endothelial cell dysfunction induced by diabetes. Vascular endothelial growth factor (VEGF) appears to be an important mediator for these early and late vascular changes. We reported previously, using skin chambers mounted on backs of SD rats, that neutralizing antibodies directed against VEGF blocked vascular permeability and blood flow changes induced by elevated tissue glucose and sorbitol levels in a dosage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 18 publications
3
12
0
Order By: Relevance
“…The main change in vascular cells has been identified to be those hyperglycemiainduced biochemical changes that are significant in causing vascular dysfunctions (Ruderman et al, 1992;Kim et al, 1994;King et al, 1994). Several lines of evidence suggest that increased vascular permeability should be one of the characteristic systemic vascular dysfunctions (Stephan et al, 1998;Fujita, 1999;Brausewetter et al, 2001). However, the integrity of the endothelium plays an essential role in controlling vascular permeability.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The main change in vascular cells has been identified to be those hyperglycemiainduced biochemical changes that are significant in causing vascular dysfunctions (Ruderman et al, 1992;Kim et al, 1994;King et al, 1994). Several lines of evidence suggest that increased vascular permeability should be one of the characteristic systemic vascular dysfunctions (Stephan et al, 1998;Fujita, 1999;Brausewetter et al, 2001). However, the integrity of the endothelium plays an essential role in controlling vascular permeability.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, the opening of the intercellular junction to macromolecules is thought to result in edema formation. It has been reported that high-glucose stimulates the formation of intercellular gaps and induces an increase of permeability in the confluent endothelium (Stephan et al, 1998;Fujita, 1999;Brausewetter et al, 2001). A number of in vitro studies have demonstrated that cell shape change or contraction involves a complex interaction between contractile elements and adhesive molecules (Moy et al, 1996;Yuan et al, 1998).…”
Section: Introductionmentioning
confidence: 97%
“…However, an increase in plasma FGF2 levels is expected in the pathophysiological condition of endothelial injury. Regarding diabetes, Stephan et al 31 showed that FGF2 is closely involved in glucose-induced vascular dysfunction. Hamed et al 32 also reported a marked increase in serum levels of FGF2 in T2DM compared with those of healthy controls.…”
Section: Glypican-5 In Diabetic Nephropathymentioning
confidence: 99%
“…Particularly, important roles for transforming growth factor-␤ (TGF-␤) (32) and connective tissue growth factor (43) have been described in diabetic nephropathy (DN). In addition, angiogenic factors such as vascular endothelial growth factor and basic fibroblast growth factor (FGF-2) were reported to contribute to the glucose-induced vascular dysfunction (34,48). Nevertheless, the importance of their nonangiogenic effects in kidney remains unclear.…”
mentioning
confidence: 99%